2010
DOI: 10.1130/b30186.1
|View full text |Cite
|
Sign up to set email alerts
|

A late Miocene-early Pliocene chain of lakes fed by the Colorado River: Evidence from Sr, C, and O isotopes of the Bouse Formation and related units between Grand Canyon and the Gulf of California

Abstract: We report strontium isotopic results for the late Miocene Hualapai Limestone of the Lake Mead area (Arizona-Nevada) and the latest Miocene to early Pliocene Bouse Formation and related units of the lower Colorado River trough (Arizona-CaliforniaNevada), together with parallel oxygen and carbon isotopic analyses of Bouse samples, to constrain the lake-overfl ow model for integration of the Colorado River. Sr iso topic analyses on the basal 1-5 cm of marl, in particular along a transect over a range of altitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 26 publications
(44 reference statements)
2
83
3
Order By: Relevance
“…This interpretation was based on: (1) strongly negative δ18O values and a wide range of δ13C; (2) offset of stable-isotope values between carbonate matrix and ostracodes in the marl unit, and a change to uniform values above the DCL; (3) cooccurrence of fresh-water, brackish, and marine organisms; and (4) similarity of isotopic values in fresh-and brackish-water ostracodes. These results are at odds with other studies that document co-variation of southern Bouse stable isotopes in mollusk shells and marl along a mixing trend from isotopically light (δ13C=−4; δ18O=−8) to seawater values (δ13C=+1; δ18O=0) (Roskowski et al, 2010;Crossey et al, 2015). Inconsistent results from different studies suggest a need to standardize sample preparation methods, which may influence interpretation of water chemistry and recognition of primary carbonate versus secondary cements and clay contamination.…”
Section: Depositional Paleoenvironments Of the Southern Bouse Formationcontrasting
confidence: 56%
See 3 more Smart Citations
“…This interpretation was based on: (1) strongly negative δ18O values and a wide range of δ13C; (2) offset of stable-isotope values between carbonate matrix and ostracodes in the marl unit, and a change to uniform values above the DCL; (3) cooccurrence of fresh-water, brackish, and marine organisms; and (4) similarity of isotopic values in fresh-and brackish-water ostracodes. These results are at odds with other studies that document co-variation of southern Bouse stable isotopes in mollusk shells and marl along a mixing trend from isotopically light (δ13C=−4; δ18O=−8) to seawater values (δ13C=+1; δ18O=0) (Roskowski et al, 2010;Crossey et al, 2015). Inconsistent results from different studies suggest a need to standardize sample preparation methods, which may influence interpretation of water chemistry and recognition of primary carbonate versus secondary cements and clay contamination.…”
Section: Depositional Paleoenvironments Of the Southern Bouse Formationcontrasting
confidence: 56%
“…However, subsequent studies have shown that 87Sr/86Sr ratios of Bouse carbonates are actually higher and more variable (0.7101-0.7123) than modern water of the lower Colorado River (0.7100-0.7101) (Roskowski et al, 2010;Crossey et al, 2015). Sr isotopes in Bouse carbonates thus record complex mixing of multiple poorly understood inputs.…”
Section: Depositional Paleoenvironments Of the Southern Bouse Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The lacustrine origin suggests deposition of the Bouse Formation in a series of lakes that fi lled and spilled from one basin to the next until system was integrated and the Colorado River was a through-fl owing river (House et al, 2005a(House et al, , 2005bSpencer et al, 2005Spencer et al, , 2008. Arguments in favor of a lacustrine origin of the Bouse Formation are based on isotopic analyses (Spencer and Patchett, 1997;Buising, 1990;Poulson and John, 2003;Roskowski et al, 2010;Spencer et al, 2013), step-like maximum elevations of the Bouse paleolakes suggesting that no uplift or southward tilting has occurred since deposition of the unit (Spencer et al, 2008(Spencer et al, , 2013, and sedimentological evidence of fl oodwater infl ux derived from northern sources immediately preceding Bouse Formation deposition in the Mohave and Cottonwood Valleys Spencer et al, 2013). An alternative interpretation suggests that the Bouse Formation accumulated in lakes along the northern part of the lower Colorado River corridor, but in the Blythe basin, the formation was initially deposited in a marine environment at the northern end of the proto-Gulf of California (Buising, 1988(Buising, , 1990.…”
Section: Introductionmentioning
confidence: 98%